Pemanfaatan Media Pembelajaran Berbasis Blog untuk Meningkatkan Kompetensi Mengetik serta Menyampaikan Ide Segala Pemikiran dalam Bentuk Ketikan pada Siswa Kelas IX pada Mata Pelajaran Informatika di MTsN 7 Agam - Junita Rosani; Hari Antoni Musril; Helmi Helmi (Lembaga Pengembangan Kinerja Dosen, 2024)
The use of web logs as a learning medium to increase interest in typing on mobile phones or computers and can issue all thoughts in the form of typing which is directly taught by UIN Sjech M. Djamil Djambek BUKITTINGGI students with the Department of Informatics and Computer Engineering Education, who are conducting Field Practice Implementation (PPL) at MTs N 7 AGAM on August 22 – November 10, 2023. manuskrip. Kemudian dilanjutkan dengan teks utama manuskrip. The use of blogs as a learning medium has not been carried out by educators with optimal informatics teachings. This is because many educators do not understand how and what steps must be taken in utilizing blogs as a learning medium. The use of blogs as a learning medium can be done at all levels both elementary, junior high, MTs, high school and vocational schools because students in general are accustomed to accessing information through the web. But in this paper, the use of blogs is more focused on junior high school / MTs and high school / vocational / MA education units because the planning of creating a blog is accompanied by steps to prepare online quizzes that will be embedded into the blog. This is done as an effort to prepare students to face UNBK. This study was conducted In this paper, described the steps in the use of blogs as a learning medium. This study begins by studying various literature and the results of similar studies to get an overview of the use of blogs as learning media. After this study, information was obtained that various problems in schools related to learning media can be overcome by utilizing blogs as learning media. In the future, it is hoped that educators can use blogs as a learning medium so that they can attract more interest and attention from students.